Dodder-transmitted mobile systemic signals activate a salt-stress response characterized by a transcriptome change in Citrus sinensis - Duan, Shuo; Xu, Zhou; Li, Xin-Yu; Liao, Ping; Qin, Hong-Kun; Mao, Ya-Ping; Dai, Wen-Shan; Ma, Hai-Jie; Bao, Min-Li (Frontiers in Plant Science, 2022)
Citrus is an essential horticultural fruit whose yield and quality are affected by salinity worldwide. The perception and adaptive regulation of citrus against salt stress were important for cultivar improvement, but the vascular system signal transduction in responding to salt stress remains elusive. In this study, we constructed the dodder (Cuscuta spp.) bridged-linked Hamlin sweet oranges (Citrus sinensis) plants to deliver the vascular signal in response to salt stress. The RNA-seq technology was applied to analyze the gene expression profiling of citrus leaves post salinity treatment. The result showed that the vascular signal was transmitted into a dodder-linked host plant to trigger a transcriptional response to salt stress. However, the phenotypic and transudative ability of the dodder was affected during the experimental process after 24 hours. 1472 and 557 DEGs were found in the salt treatment group (Group S) and the dodder-linked group (Group D), respectively, of which 454 were overlapped. The analysis results revealed that the gene expression categories in Group D represented a highly consistent expression trend to group S plants, indicating that dodder-bridged vascular signals activated the stress-response of citrus leaves for the transcriptomic reconfiguration. The KEGG pathway relationship network and key drive analysis reveal that phenylpropanoid biosynthesis, photosynthesis-antenna proteins, starch and sucrose metabolism, plant hormone signal transduction, circadian rhythm, and MAPK signaling pathway were significantly enriched as the pivot genes during salt stress. The systemic signal in the dodder-bridged host significantly regulated abiotic stress-related secondary metabolism pathways, including phenylpropanoids, lignin, and lignans. The physiological indexes of photosynthetic intensity, respiration, and attractiveness among communities supported the transcriptional change. Thus, our results indicate that the salt stress-induced vascular system signals can be transmitted through the vascular of the dodder between citrus plants, revealing the genetic regulation and physiological changes of citrus leaves responding to the plant stress signal transmission.